Low-voltage Low-power Bulk-driven CMOS Op-Amp Using Negative Miller Compensation for ECG - Muhaned Zaidi (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Two bulk-driven CMOS (Complementary Metal Oxide Semiconductor) operational amplifier (op-amp) designs for electrocardiogram (ECG) application are presented and compared in this paper. Both op-amps are based on two-stage amplification, where bulk-driven differential input is the first stage, while additional DC gain is the second stage. Different compensation techniques were integrated in each op-amp design. Standard Miller compensation was used for the first op-amp parallel with the second stage. The novelty of the second op-amp is that it utilizes negative Miller compensation between the bulk-driven input node and the output node of the first stag, while standard Miller compensation was used in the second stage. The purpose of this work was to compare DC gain, phase margin (PM) and unit gain frequency (UGF) obtained through different simulated compensation strategies and test results. The op-amps were simulated using 0.25 μm CMOS technology. The simulation results are presented using the standard model libraries from Tanner EDA tools, operating on a single rail +0.8V power supply.